Kepuasan Pengguna Pelayanan Park And Ride di DKI Jakarta (StudiPerbandingan Antara Park and Ride Terminal Ragunan dan Terminal Kampung Rambutan) - Darmawan, Rizki; Riduansyah, Mohammad (Jurnal Vokasi Indonesia, 2017)
Park and ride parking facilities support a Transjakarta bus and made for the purpose of attracting the interest of private vehicle users in order to switch to mass transit so as to reduce the use of private vehicles in the city. Satisfaction of the users is a measure of the viability and success of the park and ride which was created and is run by the Jakarta administration. The purpose of this study was to describe the customer satisfaction with park and ride facilities provided by the Jakarta administration as supporting public transportation in Jakarta. This research approach using quantitative methods with methods of data collection by spreading the questionnaire to the park and ride and a short interview. Results from the study indicate the user has been satisfied with the facilities and services provided though there are still some supporting facilities need to be improved.